The Authority of the Village Government in the Management of Village Funds during the Covid-19 Pandemic - Hamdani, Fathul; Fauzia, Ana (Indonesian Journal of Advocacy and Legal Services, 2022)
The Covid-19 emergency condition requires a change in the priority of using village funds, which was originally to finance government administration, development implementation, community development, and community empowerment switch to village cash direct assistance activities. Mekarsari Village basically had several priorities before the arrival of the Covid-19 pandemic, one of which was the improvement of infrastructure such as roads and government agencies such as village offices due to the earthquake that hit Lombok Island in mid-2018. The purpose of this study is to examine how the impact of the Covid-19 pandemic in Mekarsari Village is, then examine the authority of the Mekarsari Village Government in managing village funds in the Covid-19 pandemic era and how to optimize it, and examine what obstacles are faced by the Mekarsari Village Government in managing funds. village during the Covid-19 pandemic. In this study, the author applies the normative-empirical legal research method using a statutory, conceptual, and sociological approach. The results of the study indicate that the very broad function of the village government is the foundation for the sustainability of effective village government in carrying out local policies, especially in dealing with the Covid-19 pandemic. Then the Mekarsari Village Government has also established a village fund program to support village development so that they are able to optimally manage human and natural resources in order to alleviate new poverty due to the Covid-19 pandemic.